Calculus
posted by Katie on .
We are doing problems with the product and quotient rules, but I'm not sure if I'm doing them correctly.
If someone could check my answer I would really appreciate it.
The original problem was y = (2x1)^5 * (4x+1)^1 and I got the derivative to equal y' = [(2x1)^4/(4x+1)]/[(2x1)+ 10 /(4x+1)]

my first line after using the product rule would be
(2x1)^4(1)(4x+1)^2(4) + (4x+1)^1(5)(2x1(^4(2)
= 4(2x1)^5(4x+1)^2 + 10(4x+1)^1(2x1)^4
= (2x1)^4(4x+1)^2[4(2x1) + 10(4x+1)]
= (2x1)^4(4x+1)^2(32x + 14)
= 2(2x1)^4(4x+1)^2(16x+7)
perhaps your teacher will not insist that you completely simplify it.
I expected my students to arrive at the above answer.